2011
DOI: 10.1038/ajg.2011.156
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Ursodeoxycholic Acid Is Associated With the Development of Colorectal Neoplasia in Patients With Ulcerative Colitis and Primary Sclerosing Cholangitis

Abstract: OBJECTIVES Some studies have suggested that ursodeoxycholic acid (UDCA) may have a chemopreventive effect on the development of colorectal neoplasia in patients with ulcerative colitis (UC) and primary sclerosing cholangitis (PSC). We examined the effects of high-dose (28–30 mg/kg/day) UDCA on the development of colorectal neoplasia in patients with UC and PSC. METHODS Patients with UC and PSC enrolled in a prior, multicenter randomized placebo-controlled trial of high-dose UDCA were evaluated for the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
1
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(166 citation statements)
references
References 34 publications
3
152
1
10
Order By: Relevance
“…However, this result contrasts with studies by Sjöqvist et al and Wolf et al which found no protective effect of UDCA (Sjöqvist et al, 2004;Wolf et al, 2005). In addition, higher doses of UDCA (28-30 mg/kg body weight/day) have been recently associated to an increased risk of CAC in UC patients with PSC (Eaton et al, 2011). Therefore, at the present time, the protective role of UDCA remains controversial and it could not be recommended as a chemopreventive treatment, at least at doses higher than 15 mg/kg body weight/day.…”
Section: Ursodeoxycholic Acid Treatmentcontrasting
confidence: 55%
“…However, this result contrasts with studies by Sjöqvist et al and Wolf et al which found no protective effect of UDCA (Sjöqvist et al, 2004;Wolf et al, 2005). In addition, higher doses of UDCA (28-30 mg/kg body weight/day) have been recently associated to an increased risk of CAC in UC patients with PSC (Eaton et al, 2011). Therefore, at the present time, the protective role of UDCA remains controversial and it could not be recommended as a chemopreventive treatment, at least at doses higher than 15 mg/kg body weight/day.…”
Section: Ursodeoxycholic Acid Treatmentcontrasting
confidence: 55%
“…A prospective, randomised control trial of ursodeoxycholic acid in patients with ulcerative colitis and PSC, demonstrated significantly lower rates of colorectal dysplasia and cancer in the treatment group, with an odds ratio of 0.26 (95% CI, 0.06-0.92; P < 0.03) (Pardi et al, 2003). However other studies have not confirmed this observed reduction (Wolf et al, 2005), and a recent long-term study of patients with UC and PSC taking high dose ursodeoxycholic acid reported an increased rate of colorectal neoplasia (Eaton et al, 2011). Thus this is a controversial area and longterm ursodeoxycholic acid cannot currently be recommended as chemoprevention in patients with ulcerative colitis (Chapman et al, 2010).…”
Section: Ursodeoxycholic Acidmentioning
confidence: 54%
“…Follow-up studies have demonstrated mixed results [77][78][79], with some studies even noting an increase CRC risk in when high-doses of ursodoxycholic acid were employed [80].…”
Section: Prevention Of Crcmentioning
confidence: 99%